Variación estacional del rendimiento de extracción y actividad biológica in vitro del aceite esencial de Lippia alba (pampa orégano) - Fernández-Rosillo, Frank (2024)
Essential oils (EO) are a complex mixture of aromatic and volatile compounds, and due to their biological properties they are gaining interest as a potential and viable alternative in food production in the category of additives with a natural tendency. The objective of the research was to estimate the extraction yield in two seasons (dry and rainy season) and the in vitro biological activity of the EO of Lippia alba (pampas oregano). EO extraction was performed by hydrodistillation (Clevenger equipment), in vitro antibacterial activity was evaluated by the disk diffusion method against three bacterial species associated with food spoilage Escherichia coli, Salmonella enteritidis and Staphylococcus aureus, antioxidant capacity was determined by DPPH, FRAP, ABTS assays and the total content of phenolic compounds by the Folin-Ciocalteu method. The results showed an increase in extraction yield of 106.3% for the rainy season. The EO exhibited low activity against the bacteria studied and the antioxidant capacity showed differentiated results, for DPPH 12.24 µmol Trolox/g, FRAP 57.64 µmol Fe2+/g sample, ABTS 14.41 µmol Trolox/g sample and 72.69 mg gallic acid/g sample with respect to the content of phenolic compounds.